Pentingnya Edukasi TRIAD KRR Untuk Remaja pada Generasi Berencana - Ikhwani Saufa; Gusti Pirandy (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2023)
Adolescence is a transitional period between childhood and adulthood and has relatively not yet reached the stage of mental and social maturity so that they face conflicting emotional and social pressures. The biological and psychological development of adolescents is influenced by environmental and social developments. Adolescent problems are very complex problems, ranging from the large number of problems to the TRIAD KRR, namely adolescent reproductive health, HIV/AIDS, and drugs. To overcome this youth problem, the government has made various efforts through various programs and across institutions. BKKBN responds to these youth problems in accordance with its responsibilities in efforts to reduce population and family development, namely through family development policies. Through this Field Work Practice activity, the practitioner provides assistance by educating about the problems of TRIAD KRR, namely adolescent reproductive health, HIV/AIDS, and drugs to adolescents at Madrasah Tsanawiyah Pantai Labu. The process of providing this assistance was also carried out in the Field Work Practice II mini project, using the casework method through the general or general intervention phase consisting of Assessment, Program Planning, Intervention, Evaluation and Termination.